AS ESPACIALIDADES INSTITUINTES DAS DIFERENTES AÇÕES INFRACIONAIS COMETIDAS POR ADOLESCENTES DO SEXO FEMININO EM PONTA GROSSA-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This essay has as its guiding principle the following central question: ‘How the spatiality establishes different infractions committed by female teenagers in Ponta Grossa-PR?’. This question was drafted by the need to understand, from the geography perspective, a social group little explored in this scientific field, youngsters in conflict with the law. The operation was carried out on the basis of the Police occurrence bulletins reported to the Police Station for the Adolescents of Ponta Grossa-PR, considering the period from 2012 to 2015. Were analyzed 527 occurrence bulletins, including basic data information about authorship, victim, profile of the infraction, the spaces involved, as well as the terms of the declarations. The analyzed phenomenon shows that approximately 17% of the infraction acts in Ponta Grossa are committed by girls, which practiced the infractions with greater intensity at 15 years of age, being in your most 87% students. In addition, adolescents living in poor peripheries, in need of services and infrastructure. The General profile of the infringements found in the occurrence bulletins highlights the injury as the most common infraction in the universe of female teenagers. This represents 28% of the total number of infractions committed by adolescents in the city of Ponta Grossa-PR, but we see a growth in the universe of drug trafficking and possession of narcotic substance. The phenomenon of infractions committed by teenagers has a spatial logic of its own, because it involves different relationships between the victims and the teenagers, as well as different affections. Violence, body injury, threat and contempt and material damage kind of infractions, occur in a network of relationships, mostly with people that the teens keep a closer and personal contact. While the relationships involving the offensive act of possession of narcotic substances and drug trafficking are no longer overwhelmingly female networks, since they are classified as acts of personhood of coalition of interest as they move relations, merging personhood with subjects who have mastery over access to substances and, finally, the theft is an offensive act classified as having a dynamic spatial relations of impersonality and is soaked in rebellion and desire. Thus, we conclude that each act triggers different elements, subjects and specific spaces
Keywords: Adolescentes em conflito com a lei; Atos infracionais; Espaço urbano; Feminino; Gênero; Adolescents in conflict with the law; Infractions; Urban space; Female; Gender; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA